Smart healthcare - Gitlin, Marty (21st century skills innovation library. Exploring the internet of things., 2021)
Investigates the history, creation, and operation of healthcare technology. Highlights health tracking accessories, devices that monitor the health of persons with chronic diseases, potential problems, and future technologies. Includes a glossary and resources for further research.